EFEITO DO ÓLEO MINERAL SOBRE O FUNGO ENTOMOPATOGÊNICO Beauveria bassiana (BALLS) VUILL - Batista Filho, Antonio; Leite, Luis Garrigos; Raga, Adalton; Sato, Mário Eidi; Rossi, Marcelo Nogueira (REVISTA DE AGRICULTURA, 2015)
EFEITO DO ÓLEO MINERAL SOBRE O FUNGO ENTOMOPATOGÊNICO Beauveria bassiana (BALLS) VUILL.